Profesionalisme Pustakawan Dinas Perpustakaan dan Kearsipan di Kabupaten Soppeng - Rismadani, Rismadani; Mathar, Quraisy; Ahmad, La Ode Ismail (Maktabatun: Jurnal Perpustakaan dan Informasi, 2024)
The main problem discussed in this research is the professionalism of librarians regarding services and the professionalism of librarians regarding the development of collections in the Soppeng Regency Library and Archives Service. The aim of this research is to determine the professionalism of librarians' work in services and collection development. The data collection method uses descriptive research using a qualitative approach, namely interview, observation and documentation methods. The results of the research show that the Soppeng Regency Library and Archives Service regarding professional librarians itself is still lacking, seen from human resources which only has 3 librarians with undergraduate library education. If the service is not yet professional, it can be seen from the human resources available as well as the facilities and infrastructure. The professionalism of librarians regarding services in libraries is seen from librarians or human resources as presenters of relevant and quality information who are competent and able to provide comfortable facilities, facilities and infrastructure as well as planned systems in accordance with library management. Meanwhile, collection development has not been maximized, librarians from the Soppeng district library and archives service only take technical guidance, training and self-study on the internet, apart from that librarians must take part in community forums and library networks such as the Indonesian Librarians Association as a forum for exchanging information related to existing developments. in libraries, then by means of formal education which is able to manage information competently and professionally, scientific meetings and technical meetings in these meetings are able to increase the competence of librarians because in scientific meetings there is a learning process